Changes of the CYP11B2 Expressing Zona Glomerulosa in Human Adrenals From Birth to 40 Years of Age. Issue 11 (29th August 2022) - van de Wiel, Elle; Chaman Baz, Amir-Hossein; Küsters, Benno; Mukai, Kuniaki; van Bonzel, Lidia; van Erp, Merijn; Deinum, Jaap; Langenhuijsen, Johan
Abstract : Background: Aldosterone synthase (CYP11B2) antibodies for immunohistochemistry, enables to visualize aldosterone-producing zona glomerulosa (ZG), aldosterone-producing micronodules, and aldosterone-producing adenomas. The architecture of the ZG differs in old versus young age but the evolution of the changes is not well known. The pathogenesis of aldosterone-producing micronodules and aldosterone-producing adenomas is still unclear and research on the ZG in young populations is limited. In this study, we elucidate changes in human ZG with age by quantifying the CYP11B2 expression. Methods: We collected 83 human adrenal glands from 57 autopsy cases aged 0 to 40 years old. In 26 cases, both adrenals were available. We performed immunohistochemistry targeting CYP11B2 and quantified the relative CYP11B2 expressing area, CYP11B2 continuity, the mean gap length between CYP11B2-expressing areas and the maximum extension of CYP11B2 area (depth). Results: We found a negative correlation between age and the relative CYP11B2 expressing area, a negative correlation between age and CYP11B2 continuity, a positive correlation between age and mean gap length, and a positive correlation between age and maximum CYP11B2 depth. The changes in expression patterns of relative CYP11B2 expressing area, CYP11B2 continuity and mean gap length were seen in both adrenals of the same autopsy case. Conclusions: The decline of relative CYP11B2 expressing ZG area and continuity may indicate involution of the ZG, which is supported by an increase of gaps and maximum CYP11B2 depth indicating clustering, comparable to formation of aldosterone-producing micronodules. The similarities in both adrenals from the same case indicate that these changes occur bilaterally.